Enhancing Learning Interest through Audio-Visual Media in Early Childhood Education - Baron Santoso; Muhammad Ja'far Nashir (Didaktika: Jurnal Kependidikan, 2024)
Students who have high learning interest and motivation are usually marked by good academic grades, have structured learning habits, and have a good understanding of each reading. This study will look for the effect of audio-visual media on the learning interest of early childhood students at Raudhatul Athfal (RA) Nurul Huda, Surakarta City. This study is a collaborative classroom action research (CAR) carried out in three cycles, where each cycle consists of four main stages, namely planning, implementation, observation, and reflection. The subjects of this study were 60 class B students at Raudhatul Athfal (RA) Nurul Huda, Surakarta City. Data analysis in this study used a quantitative and qualitative descriptive approach. Quantitative data were obtained from the results of a questionnaire that measured students' learning interest, while qualitative data were obtained through observation of student activities during learning. The results showed a significant increase in students' learning interest during the three observation cycles. In cycle I, out of 60 students who were still classified as less interested in learning, there were 39 students (65%) while only 21 students (35%) showed interest. However, in cycle II, there had been a significant increase. The number of students who were less interested decreased to 27 students (45%), while students who were interested increased to 33 students (55%). This increase continued drastically in cycle III, where only 6 students (10%) were still less interested, while those who showed high interest were 54 students (90%). Effective learning does not only depend on the material presented, but also on the media used and the method of delivery that can attract attention so that it can motivate students to be more active in participating in learning activities.